The Effect of Seasonal Priming on Specific Inhalation Challenges With Birch and Grass Allergen Among Persons With Allergic Rhinitis - Ørby, Pia V.; Bønløkke, Jakob H.; Bibby, Bo M.; Ravn, Peter; Hertel, Ole; Sigsgaard, Torben; Schlünssen, Vivi (Frontiers in Allergy, 2021)
Objectives: Allergic diseases are prevalent in the working population, and work-related airborne pollen exposure might be substantial, especially among outdoor workers, resulting in work-exacerbated effects. Seasonal exposure to pollen may induce a priming effect on the allergic bronchial response resulting in exaggerated effects at the end of the natural pollen season. This was previously observed among people with asthma but may also be of importance for persons with allergic rhinitis. In this study, we examined the effect of seasonal priming on bronchial responsiveness among young adults with allergic rhinitis and no or mild asthma. In addition, we explored the association between the baseline characteristics of participants and the severity of bronchoconstriction. Finally, we evaluated the application of a novel non-linear regression model to the log-dose-response curves. Material and methods: In a crossover design, 36 participants underwent specific inhalation challenges (SICs) with either grass or birch allergen outside and at the end of the pollen season. The differences in bronchial response were evaluated by comparing the dose-response profiles and PD20 estimates derived by applying a non-linear regression model. Results: The results showed that 12 of the 19 grass pollen-exposed participants had a lower PD20 at the end of the season compared with the outside season. For birch, this was true for nine out of the 17 participants. However, no statistically significant effects of the seasonal pollen exposure were found on neither the shape nor the magnitude of the modeled dose-response curves for either birch allergen, p = 0.77, or grass allergen, p = 0.45. The model depicted a good fit for the data. Among the baseline characteristics, only the size of the skin prick test for grass allergen was associated with PD20. Conclusion: This study does not support a priming effect of pollen exposure on the bronchial response from the natural seasonal exposure levels of grass or birch allergens among young adults with allergic rhinitis.